Applying hydrological modeling to unravel the effects of land use change on the runoff of a paramo ecosystem - Cabrera Balarezo, Juan José; Crespo Sánchez, Patricio Javier; Timbe Castro, Luis; Sucozhañay Calle, Adrián Esteban (Dyna (Medellín, Colombia), 2022)
To gather insight into the impact of afforestation on the hydrology of a mountain river basin a comparative study was conducted with the objective to derive answers to the following questions: 1) How to calibrate the parameters of hydrological models subject to land use change? 2) What is the impact on peaks, total flow, and baseflow when land use gradually changes from tussock-grass to pine plantation? and 3) Is the impact different when land use changes gradually from upstream to downstream (U-D) or from downstream to upstream (D-U)? The results show that total flow, baseflow and peaks are respectively reduced by 21%, 66% and 21%. This study presents a calibration approach to quantify the effects of land use change before it is done.